1996
DOI: 10.1103/physrevb.53.r14705
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of the turnover in the vibrational frequencies of solid hydrogen at high pressures

Abstract: General rightsIt is not permitted to download or to forward/distribute the text or part of it without the consent of the author(s) and/or copyright holder(s), other than for strictly personal, individual use, unless the work is under an open content license (like Creative Commons). Disclaimer/Complaints regulationsIf you believe that digital publication of certain material infringes any of your rights or (privacy) interests, please let the Library know, stating your reasons. In case of a legitimate complaint, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
(51 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, compression also results in a significant (unexplained) intensity enhancement of the n 1 guest vibrons. The situation is made more complex through the recent result that the turnover of the Raman and infrared vibron in solid H 2 need not require charge transfer or the onset of bond weakening [22]. Finally, the isotopic spectra are shown to be of great importance for the identification of different site symmetries not easily detected in x-ray diffraction.…”
mentioning
confidence: 98%
“…Furthermore, compression also results in a significant (unexplained) intensity enhancement of the n 1 guest vibrons. The situation is made more complex through the recent result that the turnover of the Raman and infrared vibron in solid H 2 need not require charge transfer or the onset of bond weakening [22]. Finally, the isotopic spectra are shown to be of great importance for the identification of different site symmetries not easily detected in x-ray diffraction.…”
mentioning
confidence: 98%
“…In fact, the D 2 Raman frequency (scaled by √ 2) is roughly 200 cm −1 higher than that of H 2 . To first order in h, quantum corrections to the frequency are known to scale as the inverse of the particle's mass, no matter what the potential is [29]. Thus, using the experimental H 2 and D 2 frequencies, we obtain empirical but accurate quantum corrections to the classical values following Ref.…”
mentioning
confidence: 99%
“…A similar frequency shift is seen in the Raman spectrum of the hydrogen compounds. This suggests that the effect is caused by cou-pling between hydrogen molecules weakening as they are separated by the chemically inert elements [14][15][16] . A simple classical molecular potential with nearest neighbour interactions has shown that this effect is of the right order of magnitude to explain the behaviour in Argon-hydrogen mixtures 14,17 .…”
Section: Introductionmentioning
confidence: 99%